Continuous collision detection for virtual environments: A walkthrough of techniques - Sulaiman, Hamzah Asyrani; Bade, Abdullah (College of Computing and Informatics, Universiti Tenaga Nasional, 2011)
Continuous Collision Detection (CCD) has been widely accepted as the common tool to detect collision between dynamic collisions of rigid and deformable models, especially for use as an accurate collision method. Performing a computationally intensive technique for detecting between two configurations that focuses on accuracy always slows detection as compared to discrete collision detection (DCD). CCD algorithms focus on the motions toward objects regarding any interpolation as long as it can be detected before it can penetrate the object. While DCD requires backtracking after collision has been detected, CCD does not suffer the same problems as DCD. CCD also avoids the tunnelling problem that exists in DCD algorithms where penetration always occurs to the object (missed the collision). This paper will provide current and future research of CCD algorithms, which eventually will become the framework of our CCD algorithm technique for our research.